2012
DOI: 10.1007/s12149-011-0568-x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymph node accumulation on FDG-PET/CT after influenza vaccination

Abstract: Recent influenza vaccination before FDG-PET/CT examination may cause ipsilateral axillary lymph node accumulations, especially within several days after vaccination. Questionnaires about vaccination can help to avoid false interpretation of FDG avid axillary lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 18 publications
7
94
2
1
Order By: Relevance
“…The highest uptake typically occurred within the first 2 weeks after vaccination [1,3], but persisted beyond 1 month in some cases [2]. Additionally, lymph node size was normal [1][2][3][4], in contrast to our case. These reports advocate caution when considering changes to the treatment plan prior to confirmation of the suspected false-positive uptake.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…The highest uptake typically occurred within the first 2 weeks after vaccination [1,3], but persisted beyond 1 month in some cases [2]. Additionally, lymph node size was normal [1][2][3][4], in contrast to our case. These reports advocate caution when considering changes to the treatment plan prior to confirmation of the suspected false-positive uptake.…”
contrasting
confidence: 66%
“…Several previous reports demonstrated the occurrence of false-positive ipsilateral FDGavid axillary lymph nodes following vaccination [1][2][3][4]. The highest uptake typically occurred within the first 2 weeks after vaccination [1,3], but persisted beyond 1 month in some cases [2]. Additionally, lymph node size was normal [1][2][3][4], in contrast to our case.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…and s.c.) for IIV were chosen based on patterns of antigen drainage with i.p. immunization draining to the lung-draining, mediastinal lymph nodes (MedLN) (22, 23) and s.c. immunization at the base of the neck, draining to the axillary lymph nodes, similar to intradeltoid injection in humans (24, 25). We observed increased numbers of CD3 + T cells in the lungs and MedLN and increased percentages of CD44 + CD62L lo effector/memory CD4 + and CD8 + T cells in the lungs of i.n.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, such research is not being pursued elsewhere in the context of dengue, even though the value of tracking inflammation through 18 F-FDG-PET for acute viral diseases has been discussed for flu virus in both ferret and human models of infection (44,45). However, one recent case study reported an incidental 18 F-FDG-PET imaging in an adult male with DF with detectable serum viremia during an annual cancer screening (46).…”
Section: Discussionmentioning
confidence: 99%